Kinematic and Kinetic Gait Features Associated With Mild Cognitive Impairment in Parkinson’s Disease - Michela Russo; Marianna Amboni; Antonio Volzone; Sofia Cuoco; Richard Camicioli; Federico Di Filippo; Paolo Barone; Maria Romano; Francesco Amato; Carlo Ricciardi (IEEE, 2024)
Mild cognitive impairment (MCI) and gait deficits are commonly associated with Parkinson’s disease (PD). Early detection of MCI associated with Parkinson’s disease (PD-MCI) and its biomarkers is critical to managing disability in PD patients, reducing caregiver burden and healthcare costs. Gait is considered a surrogate marker for cognitive decline in PD. However, gait kinematic and kinetic features in PD-MCI patients remain unknown. This study was designed to explore the difference in gait kinematics and kinetics during single-task and dual-task walking between PD patients with and without MCI. Kinematic and kinetic data of 90 PD patients were collected using 3D motion capture system. Differences in gait kinematic and kinetic gait features between groups were identified by using: first, univariate statistical analysis and then a supervised machine learning analysis. The findings of this study showed that the presence of MCI in PD patients is coupled with kinematic and kinetic deviations of gait cycle which may eventually identify two different phenotypes of the disease. Indeed, as shown by the demographical and clinical comparison between the two groups, PD-MCI patients were older and more impaired. Moreover, PD-MCI kinematic results showed that cognitive dysfunction coexists with more severe axial symptoms and an increase postural flexion. A lack of physiological distal-to-proximal shift in joint kinetics was evidenced in the PD phenotype associated with cognitive impairments.